Chitosan–lignosulfonates sono-chemically prepared nanoparticles : characterisation and potential applications - Kim, Suyeon (2013)
Due to their recognised properties of biocompatibility, biodegradability and sustainability, chitosan nanocarriers have been successfully used as new delivery systems. In this work, nanoparticles combining chitosan and lignosulfonates were developed for the first time for cosmetic and biomedical applications. The ability of lignosulfonates to act as a counter polyion for stabilisation of chitosan particles, generated using high intensity ultrasound, was investigated. Several conditions for particles preparation were tested and optimised and the resulting nanoparticles were comprehensively characterised by measuring particle size, zeta potential and polydispersity index. The pH of chitosan solution, sonication time and the presence of an adequate surfactant, poloxamer 407, were determinant factors on the development of smaller particles with low polydispersity index (an average particle size of 230 nm was obtained at pH 5 after 8 min of sonication). The beneficial effects of lignosulfonates complex on chitosan nanoparticles were further characterised. Greater stability to lysozyme degradation, biocompatibility with human cells and antimicrobial activity was found upon lignosulfonates incorporation into chitosan nanoparticles. Furthermore, these particles were able to incorporate a hydrophilic model protein – RNase A. A burst release was observed when nanoparticles were loaded with low amount of protein while with high protein content, a sustained release was found, suggesting that the protein cargo maybe loaded both at the surface as in the bulk of the particle, depending on the concentration of drug incorporated.